2015
DOI: 10.1016/j.pacfin.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Global risk exposures and industry diversification with Shariah-compliant equity sectors

Abstract: This paper examines the risk exposures of ten major Islamic sector indexes with respect to shocks in global conventional markets. Utilizing a dynamic three-regime, three-factor risk spillover model, we generally observe positive risk exposures of Islamic equity sectors with respect to developed market shocks. Consumer Services, Oil & Gas and Technology, however, are found to exhibit negative risk exposures during crash periods, implying possible safe haven benefits for global investors. Both in-and out-of-samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…Accordingly, several studies has raised the issue of whether Islamic securities can be regarded as an alternative to conventional assets. Using a dynamic three-regime and three-factor risk spillover model, Balcilar et al (2015) show that adding Islamic equity sectors to portfolios enhances risk adjusted returns. Importantly, the authors argue that Islamic consumer services, oil and gas and information technology exhibit negative risk exposure, especially during crash periods, implying potential safe-haven benefits.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, several studies has raised the issue of whether Islamic securities can be regarded as an alternative to conventional assets. Using a dynamic three-regime and three-factor risk spillover model, Balcilar et al (2015) show that adding Islamic equity sectors to portfolios enhances risk adjusted returns. Importantly, the authors argue that Islamic consumer services, oil and gas and information technology exhibit negative risk exposure, especially during crash periods, implying potential safe-haven benefits.…”
Section: Related Studiesmentioning
confidence: 99%
“…Indeed, Islamic financial industry has experienced extraordinary growth over the last decade as the industry reached almost $1.86 trillion by the end of 2014 (Azmat et al, 2017), while the total value of Islamic finance assets under management is predicted to reach $6.5 trillion by 2020 (Balcilar et al, 2015). Islamic securities are distinctive assets that englobe only financial assets that comply with Islamic law (Shari'ah).…”
Section: Introductionmentioning
confidence: 99%
“…The role of commodities as portfolio diversifier has been studied in the literature (Balcılar et al, 2015;Mensi et al, 2016;Nagayev et al, 2016). Balcılar et al (2015) discovered significant benefits from portfolio diversification attributable to Islamic equities sectors. Specifically, the paper showed that oil & gas, technology, and consumer services have negative correlations during crisis periods, suggesting possible benefits of safe haven instruments for investors.…”
Section: Islamic Equities and Commoditiesmentioning
confidence: 99%
“…However, there are other outcomes of the risk exposure of 10 Islamic sector indices that had a positive relationship with developed market shocks and a negative relationship with three other sectors (oil and gas, technology and consumer goods) during the crisis (Balcilar et al, 2015). The findings relating to these three sectors indicate that Islamic equity provides a safe haven for investors, especially during a crisis, and also support their conclusion that Islamic finance has low-risk exposure to conventional global finance.…”
Section: Islamic Equity Investmentmentioning
confidence: 63%